Particle size, distribution, and behavior of talc preparations: within the United States and beyond. Issue 4 (July 2019) - Gilbert, Christopher R.; Haouzi, Philippe
Abstract : Purpose of review: Talc remains a common sclerosant utilized for pleurodesis. However, the use of talc has documented complications and debate has persisted regarding the safety of talc as well as the differences in talc preparations available throughout the world. We sought to describe an up-to-date review of talc preparations available and the impact these preparations may have on the safety profile of talc. Recent findings: Within laboratory-based examinations, talc particle size available within the United States appears to be more consistent with prior reported 'safe' particle sizes. The presence of talc within protein-based solutions appears to modify the overall milieu of the solution and likely results in particle aggregation. Summary: The use of talc remains well accepted for pleurodesis as evidenced by inclusion by multiple guidelines. The medical fields' current understanding of talc and its basic interactions within the pleural space remain limited. Multiple questions related to the pleural space and pleurodesis remain unanswered.